20S-ginsenoside Rg3 inhibits the biofilm formation and haemolytic activity of Staphylococcus aureus by inhibiting the SaeR/SaeS two-component system. Issue 10 (26th October 2022) - Chen, Junwen; Chen, Jinlian; Wang, Zhanwen; Chen, Chengchun; Zheng, Jinxin; Yu, Zhijian; Deng, Qiwen; Zhao, Yuxi; Wen, Zewen
Abstract : Introduction. Staphylococcus aureus is a major cause of chronic diseases and biofilm formation is a contributing factor. 20S-ginsenoside Rg3 (Rg3) is a natural product extracted from the traditional Chinese medicine red ginseng. Gap statement. The effects of Rg3 on biofilm formation and haemolytic activity as well as its antibacterial mechanism against S. aureus have not been reported. Aim. This study aimed to investigate the effects of Rg3 on biofilm formation and haemolytic activity as well as its antibacterial action against clinical S. aureus isolates. Methodology. The effect of Rg3 on biofilm formation of clinical S. aureus isolates was studied by crystal violet staining. Haemolytic activity analysis was carried out. Furthermore, the influence of Rg3 on the proteome profile of S. aureus was studied by quantitative proteomics to clarify the mechanism underlying its antibacterial action and further verified by reverse transcription quantitative real-time polymerase chain reaction (RT-qPCR). Results. Rg3 significantly inhibited biofilm formation and haemolytic activity in clinical S. aureus isolates. A total of 63 with >1.5-fold changes in expression were identified, including 34 upregulated proteins and 29 downregulated proteins. Based on bioinformatics analysis, the expression of several virulence factors and biofilm-related proteins, containing CopZ, CspA, SasG, SaeR/SaeS two-component system and SaeR/SaeS-regulated proteins, including leukocidin-like protein 2, immunoglobulin-binding protein G (Sbi) and fibrinogen-binding protein, in the S. aureu s of the Rg3-treated group was downregulated. RT-qPCR confirmed that Rg3 inhibited the regulation of SaeR/SaeS and decreased the transcriptional levels of the biofilm-related genes C opZ, CspA and SasG . Conclusions. Rg3 reduces the formation of biofilm by reducing cell adhesion and aggregation. Further, Rg3 can inhibit the SaeR/SaeS two-component system, which acts as a crucial signal transduction system for the anti-virulence activity of Rg3 against clinical S. aureus isolates.